Patient-Reported Outcomes, Experiences and Satisfaction with Weekly and Monthly Injectable Prolonged-Release Buprenorphine - Parsons G; Ragbir C; D'Agnone O; Gibbs A; Littlewood R; Hard B (Dove Medical Press, 2020)
Graham Parsons,1 Cindy Ragbir,1 Oscar D’Agnone,2 Ayana Gibbs,3 Richard Littlewood,4 Bernadette Hard5 1Turning Point, London, UK; 2The OAD Clinic, London, UK; 3Camurus Ltd, Cambridge, UK; 4applied strategic, London, UK; 5Kaleidoscope Drug Project, Cardiff, Wales, UKCorrespondence: Bernadette HardKaleidoscope Drug Project, Resolven House, Fortran Road, Cardiff CF3 0EY, Wales, UKEmail bhard@me.comIntroduction: Prolonged-release buprenorphine (PRB), administered by weekly or monthly injection, for opioid dependence (OD) treatment offers the potential to address some limitations of oral therapy including stigma, difficulty in achieving consistent appropriate dosing, risk of diversion of medications, risk of overdose, and continuing use of other drugs. Patient-reported outcomes (PRO) and experiences are important in the evaluation of OD therapy success. This work aimed to document PRO during PRB therapy to guide future treatment decision-making.Methods: Qualitative interviews were completed with people on PRB OD treatment. Twenty individuals from four treatment services in England and Wales were asked to participate. A structured interview was developed guided by a person with OD lived experience. Interviews were transcribed, coded and analyzed using iterative categorization.Results: Fifteen of 20 individuals approached agreed to participate, and 14 completed interviews. The average age of participants was 42 (range 33– 54) years, 13 males and 1 woman, the history of problematic opioid use was 14 years (3– 25 years), time in treatment was 7 years (1– 20 years), and duration on treatment with PRB was 4 months (range 1– 8 months). Participants reported treatment experiences leading to coding of 277 unique comments: therapy effectiveness (77% indicated a benefit of, or satisfaction with, PRB therapy, 7% neutral/general, 16% indicated concern or questions about PRB therapy), convenience (81% benefit, 7% neutral/general, 12% concern), and overall satisfaction (81% benefit, 3% neutral/general, 16% concern). Reported benefits include cravings reduction of 10 (71%), self-care improvement of 10 (71%), relationships improvement of 9 (64%), resources management of 6 (43%), positive outlook on life of 12 (86%). Participants reported a range of positive personal experiences; challenges reported included temporary injection discomfort at treatment initiation.Discussion: In this small, focused population, there was generally a positive level of treatment satisfaction with PRB. These experiences provide insights to explain potential treatment benefit to others and are useful in guiding therapy choices for others in the future.Keywords: opioid dependence, prolonged-release buprenorphine, patient reported outcomes